PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS BUKU KOMIK BERBANTUAN CANVA PADA MATERI PUASA RAMADHAN - Sulistiani, Ino (Institut Agama Islam Negeri (IAIN) Palopo, 2026)
Abstract This research is the results of developing comic book-based learning media. The results of canva-assisted comic book-based media design are to produce learning media in the form of printed products. The results of media and material validation meet the validity requirements of 86.6% with a very valid category. The results of the practicality test by teachers and students meet the practicality requirements, namely 85% and with a very practical category. The results of the effectiveness of comic book-based learning media can be seen from the pre-test and post-test scores of students obtained an average N-gain value of 57.7% in the